Factors influencing the intention of kedayan muslims to perform the traditional culture associated with syncretism - Mohd Mokhtar R.A.; Khalek A.A.; Sa'ari C.Z.; Mohad A.H. (Universiti Putra Malaysia, 2024)
Indexed by Scopus/ERA